A Modified Approach on Security Analysis Using Probabilistic Order Preserving Encryption Based on Cloud Data Serach (International Journal of Engineering and Computer Science, 2017)
Order preserving encryption (OPE) is an efficient tool to encrypt relevance score of the inverted index for ranked search in encrypted cloud data. From last few years cloud computing has a efficiently growing. So security is major issue for cloud computing .Existing system is based on searchable encryption (SE) with the popularity in cloud computing security and data. Considering the large number of data users and documents in cloud it is necessary for the search service to allow multi keyword query and provide results based on similarity ranking to meet effective data retrieval. In this proposed system to design secure methods of probability order preserving encryption and schemes for search in encrypted data.